Search for heavy neutral Higgs bosons produced in association with b-quarks and decaying into b-quarks at √s=13TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Brandt, Oleg; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Helary, Louis; Jongmanns, Jan; et al. (Physical review, 2020)
A search for heavy neutral Higgs bosons produced in association with one or two b-quarks and decaying to b-quark pairs is presented using 27.8 fb−1 of √s=13 TeV proton-proton collision data recorded by the ATLAS detector at the Large Hadron Collider during 2015 and 2016. No evidence of a signal is found. Upper limits on the heavy neutral Higgs boson production cross section times its branching ratio to b¯b are set, ranging from 4.0 to 0.6 pb at 95% confidence level over a Higgs boson mass range of 450 to 1400 GeV. Results are interpreted within the two-Higgs-doublet model and the minimal supersymmetric Standard Model.